Artificial Ground Motion Input Based on Structural Dynamic Compatibility. Issue 4 (April 2021) - Wu, Zuoju; Li, Honglei; Ou, Yangfang; Duan, Shusu
Abstract: The artificial ground motion input currently used is arbitrary and uncertain. It can only consider basic elements such as magnitude and preliminarily estimated epicenter distance. This is in sharp contrast with the increasingly accurate calculation of structural seismic response. It is a bottleneck for the further refinement of ground motion research. In order to solve this problem, an artificial ground motion input mode compatible with the dynamic characteristics of the target structure is constructed. It can greatly improve the safety of the building in the architectural design stage without increasing the cost excessively. Obviously, the model is more targeted, safe and reasonable.